Rural development theories and experiences - Sau Sachinandan (New Delhi Allied, 1998)
This volume consists of four sections one for each of the themes of the seminar. Section 1 presents 2 papers on the theme, Rural development theories. Section 2 includes 8 papers on the theme, Agriculture and rural development and examines issues relatin
Keywords: Rural development